2019
DOI: 10.1007/s10343-018-00441-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biostimulants on the Health Status and Content of Chlorogenic Acids in Potato Tubers (Solanum Tuberosum L.) with Colored Flesh

Abstract: The aim of this study was to evaluate the influence of cultivar and biostimulants on the health status of potato tubers after harvest and after 5 months of storage. The fungal pathogens isolated from potato tuber were cultured on PDA. The biostimulants limited the symptoms of dry rot in cv. Satina after harvest, in stored cv. Irga (Bio-Algeen S-90) and cv. Blaue St. Galler (Kelpak SL). The symptoms of common scab were reduced in stored potatoes cv. Satina in the Asahi SL treatment and the symptoms of late blig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…Our results ( Supplementary Fig. 2 ) in accordance with previous studies ( Albishi et al, 2013 , Głosek-Sobieraj et al, 2019 , Orsák et al, 2019 , Valinas et al, 2017 ), found that purple and red-pigmented tubers have a greater concentration of total phenolics, anthocyanins, and antioxidant activities. Generally, US consumers prefer white-flesh varieties of potato rather than colored flesh ( Navarre et al, 2011 ).…”
Section: Resultssupporting
confidence: 93%
“…Our results ( Supplementary Fig. 2 ) in accordance with previous studies ( Albishi et al, 2013 , Głosek-Sobieraj et al, 2019 , Orsák et al, 2019 , Valinas et al, 2017 ), found that purple and red-pigmented tubers have a greater concentration of total phenolics, anthocyanins, and antioxidant activities. Generally, US consumers prefer white-flesh varieties of potato rather than colored flesh ( Navarre et al, 2011 ).…”
Section: Resultssupporting
confidence: 93%
“…On average, it ranged from 155.7 to 188.9 mg/kg fresh weight (Tables 4-6). The obtained values are similar to those reported by other authors (Albishi et al 2013, Głosek-Sobieraj et al 2019b, Orsák et al 2019, Mystkowska et al 2020). In the present study, cv.…”
Section: Resultssupporting
confidence: 92%
“…A beneficial effect of biostimulants on the tuber content of polyphenols was also reported by other authors (Arafa et al 2012, Głosek-Sobieraj et al 2019b, Mystkowska et al 2020. Moreover, Arafa et al (2012) found a significant increase in total polyphenols following an application of biostimulants (SE 500 and HA 150) and effective microor- Satina).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In modern agriculture, natural and synthetic biostimulants, which have a positive effect on the yield of potato tubers and their quality, are used more and more often [Pavlista 2011, Mystkowska 2019]. The results of many experiments show that biostimulants regulate the physiological and morphological processes of potato plants, stimulate the development of the root system [Ahmadi Lahijani et al 2018], and strengthen the protection against abiotic stress and diseases [Bulgari et al 2019, Głosek-Sobieraj et al 2019], increase the total, commercial and nutrient yields and improve the quality characteristics of potato tubers [Pavlista 2011, Wierzbowska et al 2015, Baranowska 2018, Trawczyński 2018]. Sharma et al [2014] found that under unfavorable weather conditions, under the influence of biostimulants, the natural defense systems that stimulate plant growth and development are activated.…”
Section: Introductionmentioning
confidence: 99%